MANAGEMENT OF HUMAN CAPITAL IN THE PROCESS OF BUSINESS DEVELOPMENT - Victor A. Fursov; Natalia V. Lazareva (Вестник Северо-Кавказского федерального университета)
In the article the peculiarities of human capital is considered as a resource and incomegenerating factor of production. The author also analyzes the mechanism of the analysis of efficiency of investments in human capital. The author substantiates the basic provisions effective management of human capital of business entities, based on the need to ensure continuous learning of staff and improve the quality of working life.